Pengaruh Pemberian Insentif Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Anugerah Tangkas Transportindo - Juliyanti, Juliyanti; Asmadi, Iwan; Haryono, Bambang (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This article aims to find out the effect of providing work incentives and work motivation on employee performance at PT. Anugerah Tangkas Transportindo. This type of research is causal associative research. The variables of this research are independent variables, namely work incentives (X1), work motivation (X2), while the dependent variable is employee performance (Y). In this study, the population is only 38 people, so that all employees in the Custom Clearance division at PT. The Jakarta Transportindo Agile Award was used as a sample. The data analysis consisted of validity and reliability test, classical assumption test, multiple regression analysis, F test, and t test. The results of the data analysis show that the work incentive variable has a significant influence on employee performance. There is a significant influence between work motivation and employee performance. The variables of work incentives and work motivation have a simultaneous effect on employee performance. The results of the partial and simultaneous determination coefficient test, it can be concluded that the work incentive variable (X1) has a weak influence on employee performance by 28.9%. The variable of work motivation also had a weak influence on employee performance by 13.8%. Simultaneously, the variables of work incentives and work motivation had a not very strong influence on employee performance by 35.6%, meaning that there were still 64.4% variations in employee performance that were influenced by other factors